Uniform Estimates for Damped Radon Transform on the Plane - Youngwoo Choi (Abstract and Applied Analysis)
Uniform improving estimates of damped plane Radon transforms in Lebesgue and Lorentz spaces are studied under mild assumptions on the rotational curvature. The results generalize previously known estimates. Also, they extend sharp estimates known for convolution operators with affine arclength measures to the semitranslation-invariant case.